Spiritual Needs of Patients with a Colostomy in a Public Hospital - Rahmatia Mozaike; Chandra Isabella; Atlastieka Praptiwi (Universitas Padjadjaran, 2018)
An intestinal stoma is an opening of the intestinal tract into the abdominal wall for patients with feces production problems. The process might change patients’ physical, psychological, social, and spiritual. Patients have limitations in daily activities, changes in elimination, depression, feeling hopeless, ashamed with the colostomy bag, and may also affect to their religious and spiritual. For example their religious rituals and belief in God. The aim of this study was to identify the spiritual need of patients with a colostomy in a public hospital in Bandung. This was a descriptive quantitative study, The population was patients with a colostomy who hospitalized in a public hospital in Bandung. The samples were chosen using the accidental sampling (n=42) technique. The study instrument was Spiritual Needs Questionaire (SpNQ), that consists of 19 questions with 4 dimensions (religious needs, inner peace, existential, and actively giving). Data were analyzed using statistics descriptive and presented in a table of distribution frequency. The study found that patients with a colostomy had the spiritual need for all dimension including the religious dimension (88,1%), inner peace (57,1%), existential (54,8%), and actively giving (52,4%). Patients with a permanent colostomy had higher scores on the spiritual needs than those temporary colostomy patients. It can be concluded that the religious dimension is the highest relevance of the spiritual needs. According to this study results, it is expected that nurses can improve the spiritual services in nursing care including assessing patients’ spiritual needs and facilitating patients to fulfill their spiritual needs. The facilitation includes providing an opportunity for praying together, spiritual books, helping patients for ritual worship, establishing therapeutic communication, giving patients their own time, and creating a quiet place.